PENGARUH KEPUASAN KERJA PEGAWAI TERHADAP PELAYANAN PUBLIK PADA KANTOR KECAMATAN SANGATTA UTARA KABUPATEN KUTAI TIMUR - Robi'ah, Sayyidatur (PREDIKSI, 2016)
The purpose of this research is to know the relationship between employees work satisfaction by public services at Kantor Kecamatan Sangatta Utara Kabupaten Kutai Timur to know the relations between employees work satisfaction with public services at Kantor Kecamatan Sangatta Utara Kabupaten Kutai Timur.This research conducted in the Kantor Kecamatan Sangatta Utara Kabupaten Kutai Timur. Samples taken by the census, namely 50 respondents. A measurement of data using levels 5, covers the answer strongly agree, agree, doubt, disagree and strongly disagree. The research done by the author of the research is verifikatif or causation, i.e. the research looking for the relations between the variables for with a variable due. The appliance analysis that used Rank Spearman coefficient (RS).on the analysis of the data collected it can be concluded as follows: 1) there is no relations (Association) between job satisfaction with public services. 2) In generaly, public services doesn’t affected by the job satisfaction of employees. It can be seen by the small influence of job satisfaction (18%) in public service. Thus there is another variable which is supposed to have a strong influence on good or bad public services in Kantor Kecamatan Sangatta Utara Kabupaten Kutai Timur.